Evaluation of Antibiotic Use in Typhoid Fever Patients at Mitra Sejati General Hospital Using the ATC/DDD Method - Ndruru, Masiria; Simanjuntak, Nerly Juli Pranita; Lubis, Razoki (CV. Nusantara Scientific Medical, 2025)
The inappropriate use of antibiotics can lead to negative consequences, including the development of resistance, worsening of patient conditions, and an increased burden on healthcare services. Therefore, evaluating antibiotic use through the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) method is essential to assess the rationality of therapy, particularly for typhoid fever cases, which remain highly prevalent in Indonesia. This study aimed to evaluate the use of antibiotics in typhoid fever patients at Mitra Sejati General Hospital using the ATC/DDD method. This research was a descriptive study with a cross-sectional design, utilizing patient health records of typhoid fever cases hospitalized from January to March 2024. A total of 72 patients were selected using purposive sampling and compared to WHO standards. The results showed that ceftriaxone (34.7%), levofloxacin (19.4%), and cefixime (16.7%) were the most frequently prescribed antibiotics. Based on the ATC/DDD method, only ciprofloxacin, cefotaxime, and cefadroxil met the WHO DDD standard, while the other seven antibiotics deviated from it. In conclusion, the majority of antibiotic use for typhoid fever patients at Mitra Sejati General Hospital did not comply with WHO standards, indicating the need to strengthen monitoring systems and promote education regarding the prudent and rational use of antibiotics in healthcare facilities